Comparison of high- and low-dose radial extracorporeal shock wave therapy in carpal tunnel syndrome - Ceylan, Ismail; Kurtuncuoglu, Busra; Tuncay, Figen; Canli, Mehmet; Alkan, Halil; Tayfur, Abdulhamit (Assoc Medica Brasileira, 2025)
OBJECTIVE: The aim of this study was to compare the efficacy of radial extracorporeal shock wave therapy administered at low vs. high pressures in patients with carpal tunnel syndrome. METHODS: Patients with carpal tunnel syndrome were randomized into two groups: low-dose group and high-dose group. Each patient underwent a total of four sessions of radial extracorporeal shock wave therapy, administered once a week. The radial extracorporeal shock wave therapy was delivered at 4.0 bars for the high-dose group and 1.5 bars for the low-dose group. Both groups received conventional physical therapy program consisting of transcutaneous electrical nerve stimulation, paraffin wax, orthoses, and tendon gliding exercises, three times per week over a 4-week duration. Outcome measures included pain levels, hand grip strength, pinch strength, the Boston Carpal Tunnel Syndrome Questionnaire, and nerve conduction studies. RESULTS: Both groups exhibited improvements across all measures, except for the nerve conduction studies parameters. In the intragroup analysis, statistically significant differences were observed with small-to-moderate effect sizes for median motor distal latency, median sensory nerve conduction velocity, median sensory distal latency, and the Boston functional status subscale, all favoring the high-dose group (p<0.05). In the low-dose group, a statistically significant difference with a moderate effect size was noted solely for hand grip strength (p<0.05). CONCLUSION: High-dose radial extracorporeal shock wave therapy was significantly better than low-dose radial extracorporeal shock wave therapy with small-to-moderate effect sizes in the recovery of the function and nerve conduction studies parameters of patients with carpal tunnel syndrome.
Keywords: Carpal tunnel syndrome; Extracorporeal shock wave therapy; Pain; Electromyography; Treatment